Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T18:47:57+01:00
A)½x - 2y = 8
2x + 5y = 6

1/2x=8+2y /*2
2x+5y=6

x=16+4y
2*(16+4y)+5y=6

x=16+4y
8y+5y=6-32

x=16+4y
13y=-26 /:13

x=16+4*(-2)
y=-2

x=8
y=-2
b)½x - ¾y = 0
⅔x - 1¼y = 9

1/2x=3/4y /*2
2/3x-1 1/4y=9

x=3/2y
2/3*3/2y-1 1/4y=9

x=3/2x
-3/4y=9 /*(-4)

x=3/2x
3y=-36 /:3

x=3/2*-12
y=-12

x=-18
y=-12
kilka razy próbowałem i tyle mi wychodziło
c)3x + 4y = 1⅔
6x + 3y= 1¼

x=(5/3-4y)/3 to całe dzielone przez 3
6*(5/4-4y)/3 +3y=5/4

x=(5/3-4y)/3
-8y+3y=5/4-10/4

x=(5/3-4y)/3
-5y=5/4 /:(-5)

x=(5/3-4*(-1/4))/3
y=-1/4

x=8/9
y=-1/4